Some Properties of Lightning Ground Flashes Observed in and around Sri Lanka, and their Seasonal Variations - Liyanage, J.P.; Sonnadara, D.U.J.; Fernando, I.M.K.; Weerasekera, A.B.; Lelwala, R.; Ariyaratne, T.R. (My University, 2002)
Two lightning locating systems were utilised in obtaining the cloud-to-ground flash characteristics in Sri Lanka and in the surrounding area of the Indian Ocean. Over 5,000 flashes were recorded during the year 1999 covering 39 thunder days. The lightning data are presented in terms of polarity, multiplicity, and first return stroke peak current. The percentage of positive flashes observed in this study is fairly lower than that of temporal regions but when compared with similar studies in tropical regions there is no clear difference. Out of the 3% of the positive flashes reported, 95% were single stroke. On the contrary only 56% of the reported negative flashes were single stroke. The highest percentage of single stroke negative flashes was 74% in June and lowest was 38% in February. The monthly variation of the percentage of positive flashes ranged from 17% in June to 1% in September. The highest monthly average multiplicity of negative flashes of 2.6 was recorded in February and for all other months it was below 2. The monthly averages of the negative first stroke peak currents ranged from about 39kA in August to about 56kA in September. The data obtained in the study also clearly indicates the bias in DF data for longer distances.
Keywords: Lightning Ground Flashes; Sri Lanka; Seasonal Variations